Elderly\'s Medical Therapy Status - Malihe Saboor (University of Social Welfare & Rehabilitation Sciences, 2007)
Studies show that the elderly are more prone to chronic diseases in comparison to other age groups. Medical treatment is very common in aged people. On average, every aged person uses 4.5 prescribed and 2.1 over the counter medicines. And every year they have 12 to 17 prescriptions. Indeed, medicines are mostly used in hospitals and geriatrics. (1) the most common used medicines are: analgesics, anti-inflammatory, hypertensive drugs, cardiovascular medicines & tranquilizers. Natural trend of aging emphasizes on need of change in the way of drug administration in aged people. Because of different age-related diseases, the prescriptions and dosing of different drugs has been changed specially in hospitals and geriatrics. The changing in quality of life style in aged people has also affected the way of drug administration. In this article we emphasize treatment problems, drug side effects, physiological variations and their effects on pharmacokinetic and pharmacodynamic of drugs in aging population and we also have many suggestions for increasing health in the aged and their quality of life.